2015
DOI: 10.1002/hrm.21717
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Role Duality Experienced by HR Professionals as Both Implementers and Recipients of HR Practices: Evidence from the Indian Railways

Abstract: This study provides an innovative perspective on empirically assessing HR by focusing on the duality of HR professionals’ experiences as both implementers and recipients or internal customers of HR practices given that they are also employees of the organization. We hypothesize that HR professionals experience HR practices more favorably from an implementer perspective as compared to an internal customer perspective. These differences in experiences are likely to be influenced by HR professionals’ hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Unlike other employees, HRM practitioners are faced with the challenge of performing a dual role (Pereira & Fontinha, 2016). Given the dualistic nature of their role, HRM practitioners tend to focus on the commitment of other employees while neglecting their own.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other employees, HRM practitioners are faced with the challenge of performing a dual role (Pereira & Fontinha, 2016). Given the dualistic nature of their role, HRM practitioners tend to focus on the commitment of other employees while neglecting their own.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, HR managers also play more central and crucial roles in formulating and enacting HR practices than do line managers in many Asian countries including this study's context, South Korea (Jacoby, Nason, & Saguchi, ; Kim & Ryu, ). Hence, HR managers’ commitment to HR that ensures the proper implementation of HR practices seems to be even more crucial for the success of HR practices (Pereira & Fontinha, ; Wright, McMahan, Snell, & Gerhart, ) in this study's context. As such, strategic HRM research should pay more attention to HR managers’ commitment to HR as a focal study variable and unveil various correlates of it.…”
mentioning
confidence: 89%
“…Hence, we propose that the bundle or aggregate of HR‐specific human capital variables will serve as a key factor leading to commitment to HR (Ployhart, ). In particular, we consider three variables: (a) HR‐specific tenure (i.e., how long have they worked in the field of HR; Lee et al, ), (b) HR‐related education and expertise (i.e., whether they have intensively [as a major] studied HR related subjects at a post‐secondary institute; Ericsson & Lehmann, ), and (c) job level in HR (i.e., whether they have a stronger influence on the implementation or delivery of HR activities and services; Pereira & Fontinha, ). As discussed in Kline and Peters (), commitment represents “a psychological obligation to behave in a manner consistent with the implications of prior behavior” (p. 1991).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars conducting research in the workplace found that happy employees are productive (Armenta, Fritz & Lyubomirsky, 2017;Bakhtiar, Bahrami, Keyvanara & Kalantari, 2009;De Neve, Diener, Tay & Xuereb, 2013;Lyubomirsky King & Diener, 2005;Wesarat, Yazam, & Halim, 2014;Zarei & Hughgooyan, 2011). The challenges for HRM practitioners are two-fold-they are both implementers and recipients of human resource practices (Pereira & Fontinha, 2016). As the first and largest HR professional body in Africa, the IPM is recognized by the South African Qualifications Authority (SAQA).…”
Section: Introductionmentioning
confidence: 99%